N2 Streamlining referrals to the neurodisability feeding clinic at alder hey children's hospital. (12th September 2022) - Rivlin, Gillian; Tse, Chi; McMahon, Siobhan; Luo, Zixin; Copley, Sian; Cheng, Jeng; Nair, Manjula
Abstract : Introduction: Approximately 50% of children with neurodevelopmental problems experience challenges with feeding. Managing these children and their families presents a unique opportunity to offer a single point of care in an outpatient setting. Here, they can be reviewed by multiple professionals in a single appointment. This will include assessment, examination, investigations and initiation of management plans during one point of contact. At Alder Hey Children's Hospital, the Neurodisability Feeding Clinic aims to deliver a 'One Stop Clinic', consisting of a paediatric gastroenterologist, speech and language therapist and specialist dietician. Patients and their families can meet all relevant specialists in one setting. There is currently a 5–6 month waiting time, due to high demand. Objective/Aim: This quality improvement project aimed to streamline this service, improve waiting times and patient experience. It will ensure appropriate patients are selected for this specialist clinic, are reviewed in a timely manner and provide this 'One Stop Clinic' to offer the right advice and intervention. Method: Patients were identified using electronic records of referrals to the clinic over a six-month period. The referral was reviewed and assessed to understand the reason for referral to the clinic, prior interventions and whether an alternative pathway would be more beneficial for the patient. Results: Over six months, 33 new patient appointments were offered, 18 appointments were attended. 5 were not attended and 10 were cancelled. Reason for referral included: assessment of feeding device (28), faltering growth (12), unsafe swallow (9), feed intolerance (2), oral aversion/food refusal (6) and symptoms of vomiting/reflux and retching (8). Problematic symptoms included vomiting (7) and retching (4). These patients had multiple co-morbidities including prematurity (9), significant genetic abnormalities (12), epilepsy (10), known dysmotility/feed intolerance (1), cerebral palsy (9), and global developmental delay (23). Only 4 patients had full investigation for faltering growth, 6 had contrast studies and 12 with growth parameter monitoring prior to referral. Interventions prior to referral included dietetic input (20), specialist formula (1 type [13] and >1 type [4]), nasogastric/nasojejunal feeding (8), gastrostomy (7) and anti-reflux medication (7). Summary: The Neurodisability Feeding Clinic is an important service for children with complex needs. This clinic requires improvement to ensure that attendance is optimised, and children and their families are accessing the correct service in a timely manner. Referrals to the clinic requires a pathway to ensure the correct information is provided to the service prior to the appointment, and that simple interventions or investigations are completed prior to the appointment where necessary. Conclusion/Outcomes: We have introduced a referral proforma to clinic to ensure all information pertinent to the clinic is available. This proforma provides recommendations of interventions and investigations prior to clinic. We have sent out a parent questionnaire and feeding diary to facilitate a better understanding of the challenges experienced and to manage family expectations in clinic. We are currently arranging additional administrative support to contact families prior to clinic appointments, thereby improving attendance and providing support/advice if they are facing difficulty attending clinic.